2H/1H fractionation in lipids of the mangrove Bruguiera gymnorhiza increases with salinity in marine lakes of Palau. (1st May 2017) - Ladd, S. Nemiah; Sachs, Julian P.
Abstract: Hydrogen isotope ratios ( 2 H/ 1 H or D/H) of sedimentary mangrove lipid biomarkers can be exploited as a quantitative proxy of past salinity and water isotopes. This approach is based on the observation that apparent 2 H/ 1 H fractionation between surface water and mangrove leaf lipids increases with surface water salinity. In order to better understand the mechanisms responsible for this empirical relationship, we analyzed the isotopic composition of surface water, xylem water, leaf water and leaf lipids from Bruguiera gymnorhiza mangroves growing around eleven marine lakes and a lagoon on the rock islands of Palau, spanning a salinity range of 5–32 parts per thousand (ppt). Net fractionation increased with increasing salinity for both n C31 -alkane (0.7 ± 0.1‰ ppt −1 ) and for the pentacyclic triterpenoid lupeol (0.5 ± 0.2‰ ppt −1 ). These trends could not be attributed to changes in biosynthetic fractionation with salinity, but seem more likely to be due to increasing disequilibrium between xylem water and water vapor as salinity increases. In Palau's humid climate, this most likely causes leaf water to become less 2 H-enriched relative to surface water and to xylem water as salinity increases. This supposition is supported not only by measurements of leaf water 2 H enrichment, but also by the correlation ( R 2 = 0.66) between leaf water isotopes and those of rain water, which are assumed to be in equilibrium with water vapor isotopes, and by the dependence of leaf water isotopes on water vapor isotopes in a Péclet-modified Craig-Gordon model. These results should inform the application of sedimentary mangrove lipid hydrogen isotope ratios to infer past hydroclimatic changes.